Substantiation of choosing the design of a reactordust collector with two colliding flows - Pitak, Inna; Shaporev, Valery; Pitak, Oleg; Ponomarova, Nataliia (Eastern-European Journal of Enterprise Technologies, 2018)
The objects of this study are the dust collectors for dry gas purification ‒ devices in which hydrodynamic modes are implemented. Advantages of using such devices are: work with gases of high temperature, high degree of purification; regulation of a process of gas purification from dust due to regulation of secondary air consumption. There are no improvements for the theory of operation of apparatuses for the dry purification of a gas flow from dust. It does not provide an opportunity for a reasonable choice of the design of an apparatus and its main characteristics. We consider a design of a dust collector for dry purification of a gas flow, in which a degree of purification of a gas flow from dust reaches 97‒98.5 %, regardless of the particle size of a dispersed phase. This fact is a necessary condition for modern industry. We proposed the design of a heterogeneous reactor for a gas-solid system with two colliding flows. We determined specific features of hydrodynamics of a reactor, distribution of stay time in a reactor, and proposed a model of a reactor based on discrete Markov processes. We established experimentally that a degree of purification of a gas-dispersed flow from dust in the proposed reactor can reach 98 %. This is possible because of formation of agglomerates due to intensive interaction between particles that are larger than the particle size at the reactor inlet 3‒4 times. We proved that, compared to a suspended layer and hydrodynamic conditions in cyclones and vortex chambers, the proposed reactor has an advantage in terms of energy consumption for overcoming of resistance. This is due to the fact that in these devices spend a large proportion of energy for maintenance of particles in a suspended state, and also for pumping air through internal devices. During operation of the proposed gas-purifying dust collector, we achieved qualitative indicators, which confirm the expediency of the conducted studies and the expediency of choosing a device for dry purification of a gas flow.